PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. SINAR NIAGA SEJAHTERA CABANG TASIKMALAYA - Setia Rachmanda, Yudi; Riswandi, Dede; Agustian, Aldy; Muhammad Nur Ihsan, Adi (LP2M Universitas Perjuangan Tasikmalaya, 2024)
The purpose of this study is to: 1). Knowing the organizational commitment at PT. Sinar Niaga Sejahtera Tasikmalaya Branch. 2). Knowing the performance of employees at PT. Sinar Niaga Sejahtera Tasikmalaya Branch. 3). Knowing the influence of organizational commitment to employee performance at PT. Sinar Niaga Sejahtera Tasikmalaya Branch. The research method used in this study is descriptive and verification methods. Data collection techniques are carried out through field research and literature studies. Data analysis techniques are carried out through the analysis of the Correlation Coefficient to find the value of